2023
DOI: 10.1002/ame2.12351
|View full text |Cite
|
Sign up to set email alerts
|

Baizhu‐Baishao herb pair ameliorates functional constipation and intestinal microflora disorder in rats

Xiaojun Li,
Xiaoting Wang,
Ziyan Wang
et al.

Abstract: BackgroundIn China, Rhizoma atractylodis macrocephalae‐Paeonia lactiflora Pall (Biazhu‐Baishao, BZBS) is a classic herb pair used to treat intestinal stress syndrome, ulcerative colitis and other diseases. However, the mechanism of BZBS in the treatment of functional constipation (FC) has been little studied and remains unclear. In this study, a behavioral investigation, colon tissue morphology, enzyme‐linked immunosorbent assay (Elisa) and intestinal microflora analysis have been used to illuminate the potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 39 publications
(66 reference statements)
1
0
0
Order By: Relevance
“…We found that compared with the untreated UC model group, PE&AFWE significantly alleviated the disease activity index (DAI), improved the symptoms of hematochezia and diarrhea, and reversed the inflammatory cell infiltration. Firmicutes and Bacteroidetes were shown to be the two largest microbial communities in this study and the proportion of Firmicutes/Bacteroidetes found in this study is consistent with that previously reported 33 . The proportion of Firmicutes/Bacteroidetes decreased in UC due to colon injury.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We found that compared with the untreated UC model group, PE&AFWE significantly alleviated the disease activity index (DAI), improved the symptoms of hematochezia and diarrhea, and reversed the inflammatory cell infiltration. Firmicutes and Bacteroidetes were shown to be the two largest microbial communities in this study and the proportion of Firmicutes/Bacteroidetes found in this study is consistent with that previously reported 33 . The proportion of Firmicutes/Bacteroidetes decreased in UC due to colon injury.…”
Section: Discussionsupporting
confidence: 93%
“…1 The colon contains the highest microbial diversity and load, up to 10 12 bacteria/g feces, and the microbial density also peaks in the colon. 2 The highly stable and shared component of microbiota between individuals is known as 'core microbiota'. 3 Although pathogens are rapidly recognized and destroyed by the immune response, the host tolerates the intestinal microbiota by mechanisms that are still unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation